Entamoeba histolytica infections in wild and semi‐wild orangutans in Sumatra and Kalimantan. Issue 5 (16th March 2020) - Stuart, Peter; Yalcindag, Erhan; Ali, Ibne Karim M.; Pecková, Radka; Nurcahyo, Wisnu; Morrogh‐Bernard, Helen; Foitová, Ivona
Abstract: Key to the success of orangutan conservation management practices is the prevention of the introduction of infectious diseases to the remaining populations. Previous reports of Entamoeba spp. positive orangutans are of concern as Entamoeba spp. infection has been linked to morbidity and mortality in primates. It remains to be determined if the Entamoeba species infecting orangutans is the pathogenic Entamoeba histolytica . Orangutan fecal samples have been collected from orangutans from sites in Sumatra (Bukit Lawang, Ketambe, and Suaq, 241 samples from 64 individuals), and two sites in Kalimantan (Sebangau and Tuanan, 129 samples from 39 individuals). All samples were from wild orangutans except for a proportion from Sumatra which were from semi‐wild (108 samples, 10 individuals). E. histolytica ‐specific nested PCR assays were carried out on the fecal samples. A total of 36 samples from 17 individuals tested positive for E. histolytica . When compared with published sequences using NCBI BLAST the E. histolytica positive samples showed a 98–99% concordance. The majority (76%, n  = 36) of the positive isolates came from semi‐wild orangutans in Bukit Lawang. This study supports the growing body of evidence that contact with humans is an important risk factor for infection of wild primates with E. histolytica . Abstract : First molecular confirmation of Entamoeba histolytica in orangutans. Highlights: First molecular confirmation of Entamoeba histolytica in orangutans Results support that nonhuman primates in close proximity to humans are at a risk of E. histolytica infection Identified three gene target regions for future studies